Processos de implementação da BNCC na educação infantil: o trabalho didático pedagógico sob o olhar da linguagem corporal - Folgiarini, Andrei Minuzzi (2021)
Linked to the Postgraduate Program in Public Policies and Educational Management (PPPG) of the Federal University of Santa Maria (UFSM), this Dissertation Work is presented as a requirement for the completion of the Professional Master's Course in Public Policies and Educational Management, linked to Research Line 2 (LP2). The theme of this investigation is centered on the possibilities of curriculum elements of Body Language (LC) for Early Childhood Education (EI) and aims to investigate how the processes of implementation of the National Common Curricular Base (BNCC) occur in a Municipal School of Education (EMEI) of the Municipality of Santa Maria - RS. Our research intention is justified in generating from theorizations, a product that will enable theorizing and qualification of school times and spaces, with regard to the elements of the LC for the EI. As a research problem we have the following concern: How do the proposals contained in the BNCC imply the organization of knowledge regarding LC in an EMEI in the municipality of Santa Maria - RS? The methodological approach is qualitative, therefore, subjects and documents were used as research sources. As collection instruments, narrative interviews were conducted with four leading pedagogues. The results of this work point out theoretical and technical elements of a typical EI curricular routine, common among the four teachers: (1) Adaptation; (2) reception; (3) care, hygiene and food processes; (4) targeted and non-directed educational activities; (5) registration and observation organizations for evaluation purposes. These curricular aspects are directly related to the pedagogical didactic work in relation to the children's body movement. The teachers report difficulties in planning activities aimed at body movements, they are challenging and sometimes hampered by technical and structural issues. As for the BNCC implementation processes in the EMEI in question, although we do not identify an exact number, the teachers report several actions of the school in relation to the study of the document, however, we can conclude that the results of the training and construction processes of the Document Oriantador Curricular of Santa Maria (DOCSM) were qualitatively superior in relation to school movements aimed at BNCC. Finally, this work points out that the use of guiding documents in EI is still a challenge to be considered by managers and education professionals. The product of this research proposes training meetings with the EMEI professionals in question in order to: (1) Enable moments of appreciation and organization of knowledge attributed to Body Language described in the BNCC and by Gonzalez & Schwengber (2012), which can be thought of here. sphericity of EI through the concept of corporeality; (2) Planning and evaluation of proposals based on a reorganization of times and spaces at EMEI.